Natural infection of the ground squirrel (Spermophilus spp.) with Echinococcus granulosus in China. - Yu Rong Yang; Tianxi Liu; Xueli Bai; Belgees Boufana; Philip S Craig; Minoru Nakao; Akira Ito; Jan Zhong Zhang; Patrick Giraudoux; Donald P McManus (Public Library of Science (PLoS), 2009)
BACKGROUND: Echinococcus granulosus is usually transmitted between canid definitive hosts and ungulate intermediate hosts. METHODOLOGY/PRINCIPAL FINDINGS: Lesions found in the livers of ground squirrels, Spermophilus dauricus/alashanicus, trapped in Ningxia Hui Autonomous Region, an area in China co-endemic for both E. granulosus and E. multilocularis, were subjected to molecular genotyping for Echinococcus spp. DNA. One of the lesions was shown to be caused by E. granulosus and subsequently by histology to contain viable protoscoleces. CONCLUSIONS/SIGNIFICANCE: This is the first report of a natural infection of the ground squirrel with E. granulosus. This does not provide definitive proof of a cycle involving ground squirrels and dogs or foxes, but it is clear that there is active E. granulosus transmission occurring in this area, despite a recent past decline in the dog population in southern Ningxia.